Eros and civilization - Marcuse, Herbert (Sphere Books, 1956)
When Eros and civilization was first published in America in 1955 it was quickly recognised as an important and original re-examination of Freud's thought. The American critic, Clyde Kluckhohn commented that" Except for Ernest Jones's two notable books on Freud and his life, this strikes the reviewer as the most significant general treatment of psychoanalytic theory since Freud himself ceased publication,...